Pengaruh Financial Distress dan Pergantian Manajemen Terhadap Auditor Switching - Lutfiah Airlangga Putri; Dirvi Surya Abbas (Prosiding, 2022)
This research was aims to determine the effect of financial distress and management switching against auditor switching at mining companies listing on Indonesia stock exchange. Purposive sampling used for this research, there are 14 companies with 6 accounting period that meet the criteria in this study. The result simultaneously that financial distress and management switching have a positive effect on auditor switching. Financial distress have no significant effect on auditor switching and management switching have significant effect on auditor switching